Home market effect versus multinationals - Eric Toulemonde (Institute for the Study of Labor (IZA), 2007)
We develop a model with two asymmetric countries. Firms choose the number and the location of plants that they operate. The production of each firm increases when trade costs fall. The fall also induces multinationals to repatriate their production into a single country, which is likely to be the large country because of the home market effect. The net effect on total output is favorable in the large country and ambiguous in the small country. We extend the model to endogenize country sizes and we show that in an equilibrium with multinationals only, a rent can be taxed by governments.
urn:nbn:de:101:1-2008032859
Keywords: 330; Standortwahl; Multinationales Unternehmen; Globalisierung; Wirtschaftsgeographie; Außenwirtschaftstheorie